Key Drivers of PPPs in Electricity Generation in Developing Countries : Cross-Country Evidence of Switching between PPP Investment in Fossil Fuel and Renewable-Based Generation - Vagliasindi, Maria (World Bank, Washington, DC, 2012)
This paper presents new global evidence on the key determinants of public-private partnership investment in electricity generated by fossil fuels and renewable energy based on a panel data analysis for 105 developing countries over a period of 16 years from 1993 to 2008. It aims to identify the key factors affecting private investors' decision to enter electricity generation, through probit analysis, and the amount of investment sunk in this market segment, based on Heckman's sample selection analysis. The paper shows some evidence of switching from investment in fossil fuels to investment in hydro and renewables and within fossil fuels from oil to natural gas. An interesting result of the econometric analysis is that the likelihood of switching toward renewable investment is driven by long-run environmental factors, such as the increases in the price of oil and the introduction of the Kyoto protocol. Another interesting result is that sector governance support schemes, provided by feed-in tariffs, affect only the entry in renewable based electricity generation and have no impact in reducing the amount of investment in fossil fuel based generation. Economy-wide governance factors, including control for corruption and degree of political competition, are factored in by private investors only in the initial stage of the game when the decision to enter into the generation market is taken and not the amount of investment. This confirms that the first generations of independent power producers have been developed on the basis of long-term power purchase agreements guaranteeing a fixed rate of return, through take-or-pay clauses and/or government guarantees.